2011
DOI: 10.1160/th10-08-0528
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between platelet reactivity and infarct-related artery patency in patients presenting with a ST-elevation myocardial infarction

Abstract: Both heightened platelet reactivity and an occluded infarct related artery (IRA) on initial angiography and at the time of primary percutaneous coronary intervention (PCI) are associated with a worsened clinical outcome in patients with ST-elevation myocardial infarction (STEMI). However, the relationship between platelet reactivity and IRA patency has not yet been established. Consecutive STEMI-patients were enrolled in this study. Patients who had TIMI-flow (thrombolysis in myocardial infarction) 0 or 1 on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…In the present report, leukocytosis was an independent predictor of impaired platelet inhibition by clopidogrel. Although the relationship evidenced here is likely to be multifactorial, the present data are consistent with previous observations demonstrating the interplay among leukocytosis, fibrinogen and inflammatory status and impaired platelet inhibition by clopidogrel (4,25,31,32). Impaired platelet inhibition by thienopyridines might trigger an inflammatory state.…”
Section: Interplay Between Impaired P2y 12 Inhibition and Inflammatiosupporting
confidence: 92%
“…In the present report, leukocytosis was an independent predictor of impaired platelet inhibition by clopidogrel. Although the relationship evidenced here is likely to be multifactorial, the present data are consistent with previous observations demonstrating the interplay among leukocytosis, fibrinogen and inflammatory status and impaired platelet inhibition by clopidogrel (4,25,31,32). Impaired platelet inhibition by thienopyridines might trigger an inflammatory state.…”
Section: Interplay Between Impaired P2y 12 Inhibition and Inflammatiosupporting
confidence: 92%
“…17) In addition, other previous studies have shown that various pro-thrombotic and inflammatory markers including the neutrophil to lymphocyte ratio, platelet count and reactivity, mean platelet volume, and uric acid have been associated with the patency of IRA in patients with STEMI before primary PCI. [8][9][10] Although the precise reasons for the difference in the factors of pre-PCI coronary flow between the present study and previous studies are unknown, differences in the cohorts, study definition, and patient backgrounds may have been the causes.…”
Section: Discussionmentioning
confidence: 70%
“…7) Previous studies have shown that various prothrombotic and inflammatory markers including the neutrophil to lymphocyte ratio, platelet count and reactivity, mean platelet volume, and uric acid have been associated with the patency of IRA in patients with STEMI before primary PCI. [8][9][10] However, factors associated with preprocedural Thrombolysis In Myocardial Infarction (TIMI) flow have not been fully investigated. The aim of this study was to examine factors associated with preprocedural TIMI flow in patients with STEMI.…”
Section: Pre-procedural Timi Flow In Stemi Patientsmentioning
confidence: 99%
“…This is especially important in patients with STEMI because of plaque rupture, high thrombus burden and increased platelet activation [8], [10]. Moreover, there are chronic processes leading to delayed endothelial healing, vessel remodelling and stent malapposition [8], [11].…”
Section: Introductionmentioning
confidence: 99%